The current and future roles of neonatal infection surveillance programmes in combating antimicrobial resistance. Issue 11 (November 2015) - Cailes, Benjamin; Vergnano, Stefania; Kortsalioudaki, Christina; Heath, Paul; Sharland, Mike
Abstract: Neonatal sepsis is an important cause of morbidity and mortality, particularly in premature or low birth weight babies. Hospital-acquired blood stream infections represent a significant and largely preventable cause of disease in this population. Neonatal units have been identified as a common site for the development and transmission of antimicrobial-resistant pathogens, a significant issue in modern medicine. Neonatal surveillance programmes collect prospective data on infection rates and may be used to optimise therapy, benchmark practice and develop quality improvement programmes. Despite this, the number of networks is relatively few and these are largely concentrated in resource-rich nations. Furthermore, surveillance definitions may vary between programmes impairing our ability to draw comparisons between them. Better harmonisation is required between networks to ensure that they achieve their potential as a valuable tool for benchmarking of hospital-acquired infection rates between units.